Implementation of Character Education in the English Learning Process - Sitti Fitriawati (Sintuwu Maroso Journal of English Teaching, 2023)
Abstract: This research discusses the implementation of character education in English learning in the tenth grade of SMK GKST Poso. This type of research uses a case study approach, the research type’s qualitative research. The subjects of this research limited by focusing on one English teacher in the tenth grade at SMK GKST Poso 2019/2020 Academic Year. The instruments used in this research were observation, documentation and interviews. Based on the results of the research that the implementation of character education in the English learning process for the tenth grade at SMK GKST Poso has been carried out by teachers through planning. In learning planning is the existence of character values contained in lesson plan, namely in core competencies and basic competencies. There areseveral inhibiting factors experienced by teachers in English learning, namely the lack of awareness of students in obeying the rules, the motivation of students to learn is still lacking and student awareness of the responsibility of the tasks given. The efforts made by the teacher in implementing character education in the learning process, namely giving exemplary time discipline, obeying the rules andfasting curiosity through apperception, as well as in the observation of the teacher also implements independent values, hard work and concludes learning outcomes to install value of confidence.